Effects of Stunting on the Decreased Cardiorespiratory Fitness of Children Aged 9 to 11 Years in Bandar Lampung, Indonesia - Nurmalasari, Yesi; Anggunan, Anggunan; Putri, Devita Febriani; Siagian, Ellys Tahnia (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2023)
Introduction: The impact of low cardiorespiratory fitness levels can increase cardiovascular disease and other degenerative diseases. Children with stunting need attention to cardiorespiratory fitness levels. Purpose: This study aims to determine the effect of stunting on cardiorespiratory fitness in children aged 9-11 years. Methods: This type of research is observational analytic with a cross-sectional design. The sample of this study was 77 elementary school children who were taken using consecutive sampling techniques. Measurement of the research variable cardiorespiratory fitness level using the modified Harvard step test and the stunting variable measured using the child's Body Length/Height measurement index, stunting if the measurement is at the threshold of -3SD to < -2SD. Data were analyzed by the Spearman test. Results: A total of 77 children were found to be stunted, with a cardiorespiratory fitness level of 92.3% and a poor level of 7.7%. Meanwhile, children in the non-stunting category had 23.7% less cardiorespiratory fitness and no poor fitness. The analysis results show a relationship between stunting and cardiorespiratory fitness in children (p=0.000), which is a very strong relationship (r=0.917). Conclusion: Stunting in children has a chronic effect on cardiorespiratory fitness. It is necessary to improve cardiorespiratory fitness in children with measurable physical exercise and improved micronutrients to prevent early impact on adulthood. Latar Belakang: Dampak tingkat kebugaran kardiorespirasi yang rendah dapat meningkatkan penyakit kardiovaskular dan penyakit degenerative lain. Anak dengan stunting perlu mendapatkan perhatian tingkat kebugaran kardiorespirasi. Tujuan: Penelitian ini bertujuan untuk mengetahui efek stunting dengan kebugaran kardiorespirasi pada anak usia 9-11 tahun. Metode: Jenis penelitian ini bersifat analitik observasional dengan desain cross sectional. Sample penelitian ini adalah anak SD berjumlah 77 orang yang diambil menggunakan teknik consecutive sampling. Pengukuran variabel penelitian tingkat kebugaran kardiorespirasi mengunakan Harvard step test yang dimodifikasi dan variabel stunting diukur menggunakan indeks pengukuran PB/ TB anak, stunting jika pengukuran berada pada ambang batas -3SD sd < -2SD. Data dianalisis dengan uji Spearman. Hasil: Partisipan total 77 anak menemukan dengan kategori stunting yang mengalami kebugaran kardiorespirasi level kurang 92,3% dan level buruk 7,7%. Sedangkan, anak kategori tidak stunting terdapat anak dengan kebugaran kardiorespirasi kurang 23,7% dan kebugaran buruk tidak ditemukan. Hasil analisis menunjukkan terdapat hubungan stunting dengan kebugaran kardiorepirasi pada anak (p=0,000) dengan hubungan sangat kuat (r=0,917). Simpulan: Stunting pada anak memberikan pengaruh yang kronis pada kebugaran kardiorespirasi. Perlu meningkatkan tingkat kebugaran kardiorespirasi pada anak dengan latihan fisik yang terukur maupun peningkatan gizi mikro untuk mencegah sejak dini dampak pada masa dewasa.